2016
DOI: 10.1007/s10461-016-1650-0
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Use Pre-Exposure Prophylaxis (PrEP): An Empirical Test of the Information-Motivation-Behavioral Skills (IMB) Model among High-Risk Drug Users in Treatment

Abstract: Evidence from recent pre-exposure prophylaxis (PrEP) trials has demonstrated its safety and efficacy in significantly reducing the risk of HIV acquisition for those who are at considerable risk of acquiring HIV infection. With a rapid increase in the amount of research on the efficacy of PrEP for HIV prevention, complementary research on the willingness to use PrEP has grown, especially among MSM, but limited research has been focused among people who use drugs (PWUD). As part of the formative process, we util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…With increasing levels of opioid use and injection in many areas of the United States, 31,32 the introduction of even one case of HIV into PWID networks has the potential to rapidly spread HIV, 5 threatening the large strides made toward HIV prevention. Although there is a vast and growing literature on PrEP knowledge and interest among MSM, 33,34 few studies [10][11][12][13][14][15] and no in-depth qualitative examinations-have explored PrEP knowledge and interest among PWID. In our qualitative study among PWID in the US Northeast, where HIV transmission attributed to injection drug use appears to be increasing, 20 we found that knowledge of PrEP was extremely low, and interest in using PrEP was mixed and depended on prior PrEP knowledge and HIV risk perceptions that were complex and suboptimal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With increasing levels of opioid use and injection in many areas of the United States, 31,32 the introduction of even one case of HIV into PWID networks has the potential to rapidly spread HIV, 5 threatening the large strides made toward HIV prevention. Although there is a vast and growing literature on PrEP knowledge and interest among MSM, 33,34 few studies [10][11][12][13][14][15] and no in-depth qualitative examinations-have explored PrEP knowledge and interest among PWID. In our qualitative study among PWID in the US Northeast, where HIV transmission attributed to injection drug use appears to be increasing, 20 we found that knowledge of PrEP was extremely low, and interest in using PrEP was mixed and depended on prior PrEP knowledge and HIV risk perceptions that were complex and suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients engaged in methadone treatment for opioid use disorder, an intervention based on an Information-Motivation-Behavioral skills model of PrEP uptake resulted in increased willingness to use PrEP. 15,57 This model emphasized the need for at-risk individuals to have information (accurate, factual knowledge of HIV transmission and PrEP efficacy, safety, and dosage), motivation (perceived HIV risk and positive healthcare attitudes and personal intentions), and behavioral skills (self-efficacy for obtaining and using PrEP, action planning for PrEP consultations, screening appointments, and adherence). 58 However, the appropriateness of this model for out-of-treatment individuals with current injection drug use should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop effective intervention to promote PrEP, it is important to understand factors associated with willingness to use PrEP among GBMSM with experience of SDU. At least three quantitative studies investigated factors associated with willingness to use PrEP among high-risk drug users [30][31][32]. These studies had found a number of factors to be associated with willingness to use PrEP, including age, types and frequency of drug use, perceptions of HIV risk and PrEP (e.g., perceived effectiveness, would be less worried if on PrEP, concerns related to side effects, and confident to use/adhere to PrEP) [30][31][32].…”
Section: Introductionmentioning
confidence: 99%